HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) DENGAN TES FUNGSI PARU - Rujito, Lantip; Ristianingrum, Ika; Rahmawati, Indah (MANDALA of Health, 2010)
Body mass index (BMI) is a tool of measuring the nutritional status of individu. One of the effects ofobesity is the mechanics disturbance led to abnormality on pulmonary function tests. This study was aimed todetermine the relationship between body mass index with pulmonary function tests (PFTs) on medical studentJenderal Soedirman University. Analityc observational study with cross sectional design was used in thisinvestigation. The sampling technique used proportional random sampling with 82 samples. Pulmonaryfunction tests was classified into vital capacity (VC), tidal volume (TV), inspiration reserve volume (IRV),expiratory reserve volume (ERV), inspiration capacity (IC), forced vital capacity (FVC) dan FEV1.Univariate analysis, which was using table of frequency to see chategorichal variables and central tendencymeasurement to see numerical variables, and bivariate analysis, which was using Pearson and Spearmancorrelation to see the relationship between BMI with PFTs; unpaired t tests and Mann Whitney to know thedifferences of PFTs results between men and women, were used in this research. From the results weconcluded that there are significant relationship between between BMI with VC (p = 0,015), IRV (p = 0,026),IC (p = 0,016), FVC (p = 0,004) and FEV1 (p = 0,021) with low power relationship and was no relationshipBMI with TV (p = 0,489) and ERV (p = 0,231). In the unpaired t test and Mann Whitney we found that thereare differences all PFTs in a group of men and women.